The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physreva.77.032346
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of entanglement in the anisotropic Heisenberg(XXZ)model

Abstract: We have applied our recent approach (Kargarian, et.al Phys. Rev. A 76, 60304 (R) (2007)) to study the quantum information properties of the anisotropic s=1/2 Heisenberg chain. We have investigated the underlying quantum information properties like the evolution of concurrence, entanglement entropy, nonanalytic behaviours and the scaling close to the quantum critical point of the model. Both the concurrence and the entanglement entropy develop two saturated values after enough iterations of the renormalizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
92
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 37 publications
7
92
0
Order By: Relevance
“…The pairwise entanglement of the system is also discussed by means of quantum renormalization group (QRG) method [16,17]. Very recently, the spin−1/2 Ising and Heisenberg models are studied by using the same method by a group of Iran and found that the systems exist QPT [18][19][20][21]. It is also shown that the nonanalytic behavior of the entanglement and the scaling behaviors closing to the quantum critical point are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The pairwise entanglement of the system is also discussed by means of quantum renormalization group (QRG) method [16,17]. Very recently, the spin−1/2 Ising and Heisenberg models are studied by using the same method by a group of Iran and found that the systems exist QPT [18][19][20][21]. It is also shown that the nonanalytic behavior of the entanglement and the scaling behaviors closing to the quantum critical point are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, we consider the thermodynamic limit via PCUT and probe phase transitions in spatial dimensions d = 1, 2, and 3. Despite its local nature, nonanalytic behavior of derivatives of concurrence signals a phase transition in the system, and its scaling in the vicinity of critical points is connected to the universality class of the model [19][20][21] . We will show that concurrence does not capture the critical properties of the KN model at the mentioned spatial dimensions, manifesting that the underlying correlations are not of the bipartite nature.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, A. Osterloh et al first introduced the density matrix renormalization-group (DMRG) approach to study the entanglement close to the quantum phase transition (QPT) [20] and reveal a profound difference between classical correlations and the non-local quantum correlation. Further,by applying the quantum renormalization-group (QRG) approach, M. Kargarian et al investigated the entanglement in the anisotropic Heisenberg model [21,22] and discussed the nonanalytic behaviors and the scaling close to the quantum critical point of the system. Recently We have calculated the block-block entanglement in the XY model without and with staggered Dzyaloshinskii-Moriya (DM) interaction by using this QRG method and have found the DM interaction can enhance the entanglement and influence the QPT of the system [23,24].…”
Section: Introductionmentioning
confidence: 99%